Three Neoclassicisms. Exploring the Possibilities of a Comparative Average Shot Length Through Clint Eastwood, Brian De Palma and Woody Allen - Agustín Rubio Alcover; Adrián Tomás Samit (La Revista Icono 14, 2013)
This study is intended to compare the complete filmographies of the three American directors whose works are analyzed. They are Clint Eastwood, Brian De Palma and Woody Allen. We define the approach as a trampoline for leaping over the wall of a difficult conceptual and methodological blind alley—an understanding of movie editors and their task, but above all their contribution. Their work is disguised as something merely technical and obvious but, even in the best of cases, this attitude never anything other than lazy. It is the analysis route upheld and cultivated by the David Bordwell and Barry Salt that we are prepared to travel along. If we want to abjure an unsustainably radical anti-empiricism without precipitating ourselves into neo-empiricist infantilism or regressing to a chaotic teratology—that is: to try to remain focused on both the wood and the trees—a statistical-type study, aided by the latest-generation digital and computer tools and, more specifically, an Average Shot Length study (which we will refer to from now on with the acronym ASL) appears to us an objective and, consequently, literally unobjectionable criterion. It is probably as reductionist as it is stimulating when it comes to reaching conclusions that are non-definitive but undoubtedly worthy of interest, because, faced with the subjectivity of the analysis and at the general macroscopic level of the movie, the normative and the standard blends with the deviant, or exceptional.